2011
DOI: 10.1063/1.3671999
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of recombination mechanisms and strength on processing conditions in polymer solar cells

Abstract: Charge carrier recombination due to carrier trapping is not often considered in polymer based solar cells, except in those using non-fullerene acceptors or new donor polymers with limited short-range order. However, we show that even for the canonical poly(3-hexylthiophene): phenyl-C61-butyric acid methyl ester (P3HT:PCBM) system, relative strengths of bimolecular and trap-assisted recombination are strongly dependent on processing conditions. For slow-grown active-layers, bimolecular recombination is indeed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…The average PCE of the B‐DTS was 4.17% ± 0.67%. The PCE distribution of the B‐DTS was comparable to the previously reported PCE values of DTS based OPVs utilizing the same device structure, additives, and electrode . Another control device of the B‐D130 exhibited maximum PCE of 5.03% with V OC , J SC , FF values of 0.97 V, 8.99 mA cm −2 , 0.57, respectively.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The average PCE of the B‐DTS was 4.17% ± 0.67%. The PCE distribution of the B‐DTS was comparable to the previously reported PCE values of DTS based OPVs utilizing the same device structure, additives, and electrode . Another control device of the B‐D130 exhibited maximum PCE of 5.03% with V OC , J SC , FF values of 0.97 V, 8.99 mA cm −2 , 0.57, respectively.…”
Section: Resultssupporting
confidence: 82%
“…The slope of V OC versus ln( I ) is known to approach k b T / q when bimolecular recombination (Langevin recombination) is dominant. A stronger dependence on light intensity is expected for trap‐assisted recombination, i.e., a slope greater than k b T / q . As shown in Figure c, the value for B‐DTS deviated significantly from that expected in ideal devices and was determined to be 5.0 k b T / q .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Increasing power intensity, the bimolecular recombination becomes dominant. 34 Fig. 5 also showed the dependence of FF upon power intensity, where FF of 0.74 under 100 mW/cm 2 was observed.…”
mentioning
confidence: 80%
“…3(c). In case of bimolecular recombination of free carriers being the only loss mechanism, it has been shown that the Voc is given by 27 Voc…”
Section: -2mentioning
confidence: 99%